A scoping review on the conceptualisation and impacts of new mobility services - Mubiru, Ibrahim; Westerholt, René (Technische Universität Dortmund, 2024)
In the course of major societal developments such as digitalisation and increasing urbanisation, various forms of so-called new mobility services have emerged. Various disciplines are engaged in understanding these services. However, what is still missing is a comprehensive understanding of what the umbrella term new mobility services means beyond a loosely used catch-all term. This article provides an interdisciplinary overview of the concept of new mobility services and their respective impacts on mobility landscapes. These aspects are summarised using a scoping review approach by examining a total of 98 publications. Our results show that the term new mobility services is indeed an umbrella term for different mobility concepts that are conceptualised differently and whose impacts on mobility landscapes are manifold. However, by applying elements of formal concept analysis, we can identify several key characteristics that define the lowest common denominator for services to be classified as new mobility services.
European transport research review; 16
Keywords: New mobility services; Shared mobility services; Micro mobility services; Conceptual modelling; Transport planning; 710